The Role of Parents in the Sexual Education of Children Aged 5-6 Years in Marenu Village, Aek Nabara Barumun District, Padang Lawas Regency - Aslamia Pulungan; Srinahyanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to describe the role of parents in the sexual education of older children aged 5-6 years in Marenul Village, Aek Nabara Baru District, Padang Lawas District. The research method used is a qualitative method by using data collection techniques through observation and interviews. Subjects in this study were 8 elderly people out of 32 elderly people. The data analysis technique used in this research uses the Miles and Hulberman model, namely data collection, data reduction, data presentation, and conclusions. The findings of this study are the role of parents in the sexual education of children in the village of Marenul Suldah either, which can be seen from their role as positive role models (wearing clothes that cover their private parts, exemplifying how to clean their genitals, exemplifying how to care for their own tulbulh), as child supervisors. good ones (supervising the child's environment, selecting friends, supervising children's viewing either from smartphones or television, supervising children's friends of the opposite sex and providing religious education). As a good guide, (prohibiting other people from touching their tulbulh, limiting children's association, prohibiting touching the genitals of friends of the opposite sex), and as a giver of good understanding (introducing tulbulh members, giving an understanding of the awareness that tulbulh given by the creator must be maintained and cared for, providing an understanding of sexual education with interesting media).